Quantification of sinigrin in two species of cleome l.(cleomaceae) using hplc - LAKSHMI S. PILLAI (International Journal of Pharma and Bio Sciences, 2018)
The genus Cleome belongs to the family Cleomaceae. Most of the species of the genus are considered to be weeds but some are reported to possess nutritional and medicinal properties. The present investigation deals with the quantification of sinigrin, in the methanol extracts of two species of Cleome, Cleome viscosa L. and C. burmanni W. & A. using HPLC. Sinigrin is reported to be the precursor of the anticancer compound, allylisothiocyanate and possesses antimicrobial property. HPLC analysis confirmed the presence of sinigrin in both the species. Cleome viscosa contained higher amounts of sinigrin (21.35mg/g extract) than C. burmanni (17.02mg/g extract). Eventhough, sinigrin has been subjected to extensive research in recent years, isolation protocols have not yet been standardised for sinigrin. The two species of Cleome can serve as alternative sources for the isolation of sinigrin due to their abundance and availability.